The prescription of the criminal action in Canon Law - STOKŁOSA, MAREK (Prawo Kanoniczne, 2013)
The common weal of a community of the People of God requires for all the faithful of the Catholic Church the keeping of the law of God and of the Church. The violation of this law may interfere in the rights of a physical or juridical persons or the legal norms issued primarily for the sake of the public good. Quite often, this violation constitutes an offense, as the perpetrator commits a forbidden criminal act, for which the juridical sanction is foreseen. The reaction for the violation of the rights of physical or legal persons are legal proceedings, which initiation is dependent upon the will of the victim. In the case of a violation of the norms of criminal law should be the initiation from the office (ex officio) of the criminal process to impose the appropriate punishment to the offender. This imposition aims at restitution of the scandal and of justice and the improvement of the offender. After having exhausted the means mentioned in can. 1341, the competent authority to initiate criminal trial is the Ordinary (Can. 1718 § 1.1º), who takes the decision to refer the matter to the court or administration. Initiation of the juridical proceedings involves presentation of the accusations to the suspect, which, however, can not be dragged on too long in time. When the specified period of time, since the offense was committed, has passed, then there is a expiration of the criminal complaint, and thus the lapse of the right to punish the offender. The legislature KPK/83 in can. 1362 § 1, depending on the weight of the crime, provides four different laps of time required for the existence of expiration. The essential complement to these regulations are Normae de gravioribus delictis of 2001, which have been modified May 21, 2010 by Pope Benedict XVI. These norms not only reserve for the CDF the most serious crimes, but also define the lapse of the expiration of criminal complaints for offenses that are reserved, along with the possibility of repeal. This means that criminal responsibility for serious crimes which cause great scandal, even after several decades, may not be time-barred.